Social cost of non-medical use of psychotropic substances - Shurghaia, Eteri; Nikoleishvili, Elza (Caucasus Journal of Health Sciences and Public Health, 2018)
Achievements in the sphere of pharmacy and development of pharmaceutical industry incited in world production of strong psychotropic medicines that in case of proper use improve the quality of patient's life, however, irrational or /and inappropriate use of those medicines can cause severe impairment of health and/or psychotropic addiction. The problem of the use of psychotropic substances for non-medical purposes is the one of the serious challenges of modernity, and directly or indirectly, the consequences of illegal turnover of psychotropic substances and non-prescribe use concerns each person. The growing tendency of using psychotropic substances for non-medical purposes is a global health problem which true magnitude is unknown. In Europe, the use of benzodiazepines for non-medical purposes varies between 11% -70% among the recipients of the substitution therapy. In 2013, 1.5 million analgesics, 1.2 million tranquilizers, 603 thousand stimulants and 128 thousand sedatives were used for non-medical purposes in the United States. The research examining association between the use of psychoactive substances for non-medical purposes and suicide attempts was done. 7.5% of the researched teenagers had non-prescribed opioids, and 4.8% of them had non-prescribed sedatives. The outcomes of study revealed association of mental disorders and suicide attempts with non-medical use of opioids and sedatives. In Georgia, 10.8% of interviewed men and 9.6% of women mentioned that at least once in their life they used psychotropic medicines without a prescription. Of 400 survey participants who used psychotropic medicines without a prescription, 169 had purchased it at the pharmacies. About 12% of respondents believe that tranquilizers / sedatives are one of the most accessible means for achieving narcotic healing, 11% consuming psychotropic medicines without a prescription, 25% mentioned that their friends receive tranquilizers or sedatives without a prescription. Due to the fact that special regulations are needed to calculate the economic and social costs, the existence of assessment of costs related to abuse of substances is reasonable. In terms of problems actuality, the purpose of this cost-of-illness study is the estimation of impact of non-medical use of psychotropic substances on the material welfare of a society by examining the social cost of treatment, prevention, research, low enforcement and lost productivity. This prevalence based cost-of illness study which will be performed in the retrospective way by means of bottom-up approach, will estimate the direct and indirect costs of morbidity and mortality caused by non-medical use of psychotropic substances.